2004
DOI: 10.1186/1471-2407-4-73
|View full text |Cite
|
Sign up to set email alerts
|

CD155/PVR plays a key role in cell motility during tumor cell invasion and migration

Abstract: Background: Invasion is an important early step of cancer metastasis that is not well understood. Developing therapeutics to limit metastasis requires the identification and validation of candidate proteins necessary for invasion and migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
212
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(225 citation statements)
references
References 44 publications
12
212
0
1
Order By: Relevance
“…23 , 24 Likewise, we found high levels of TIGIT expression on CD8 + and CD4 + TILs from patient tumor samples. Moreover, the level of PD-1 expression in these samples was similarly elevated, supporting the notion of cancer immune evasion via the upregulation of inhibitory molecules.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…23 , 24 Likewise, we found high levels of TIGIT expression on CD8 + and CD4 + TILs from patient tumor samples. Moreover, the level of PD-1 expression in these samples was similarly elevated, supporting the notion of cancer immune evasion via the upregulation of inhibitory molecules.…”
Section: Discussionmentioning
confidence: 50%
“…16 In the clinical setting, prior studies have demonstrated an elevated expression of CD155 on human GBM cells and increased TIGIT expression on patient CD8 + tumor-infiltrating lymphocytes (TILs), rendering this pathway as a potential therapeutic target. 23 , 24 However, the effect of TIGIT blockade as a treatment strategy remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously established functional proteomic screens targeting the surface proteome of invasive cancer cells Sloan et al, 2004) to identify novel molecules required for invasion. In this study, we describe the identification of neuropilin-1, a receptor for the semaphorin family of axon guidance molecules, as pro-migratory and address its role in GBM cell migration.…”
Section: Introductionmentioning
confidence: 99%
“…18 However, unlike HSV-1, BHV-1 is unable to bind to host nectin-2, but is capable of recognizing the poliovirus receptor CD155, 18 a receptor associated with tumor cell migration and invasion. 19 One of the interesting features of BHV-1 is its strict host range compared with other herpesviruses, including HSV-1. Of particular interest is the inability of BHV-1 to productively infect human cells, 20 supported by the lack of reports of either productive BHV-1 infection or even 21 In this study, we determined the ability of BHV-1 to replicate, cause cytopathic effects and affect cellular viability in a panel of normal, immortalized and transformed human cells from a variety of histological origins.…”
Section: Introductionmentioning
confidence: 99%